Intra-cluster globular clusters around NGC 1399 in Fornax? - Schuberth, Y. (2008)
Aims. We investigate whether the globular clusters (GCs) in the recently published sample of GCs in the Fornax cluster by Bergond and coworkers are indeed intra-cluster objects. Methods. We combine their catalogue of radial velocity measurements with our CTIO MOSAIC photometry in the Washington system and analyse the relation of metal-poor and metal-rich GCs with their host galaxies. Results. The metal-rich GCs appear to be kinematically associated with their respective host galaxies. The vast majority of the metal-poor GCs found in between the galaxies of the Fornax cluster have velocities that are consistent with their being members of the very extended NGC 1399 GC system. We find that when the sample is restricted to the most accurate velocity measurements, the GC velocity dispersion profile can be described with a mass model derived for the NGC 1399 GC system, within 80kpc. We identify one "vagrant" GC whose radial velocity suggests that it is not bound to any galaxy unless its orbit has a very large apogalactic distance.